2017
DOI: 10.3846/16486897.2017.1284665
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Use of Peat and Charred Material in Growing Media – An Option to Reduce the Pressure on Peatlands?

Abstract: Peat is used as a high quality substrate for growing media in horticulture. However, unsustainable peat extraction damages peatland ecosystems, which disappeared to a large extent in Central and South Europe. Furthermore, disturbed peatlands are becoming a source of greenhouse gases due to drainage and excavation. This study is the result of a workshop within the EU COST Action TD1107 (Biochar as option for sustainable resource management), held in Tartu (Estonia) in 2015. The view of stakeholders were consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 58 publications
0
71
0
Order By: Relevance
“…Biochar and HTC char have physical and chemical properties that are variable, depending on the raw material used and the carbonization technique. Usually, the electrical conductivity (EC) and pH values are similarly low in peat and HTC and are slightly increased in biochar [25].…”
Section: Biochar and Hydrothermal Carbonization Products As Bioresourmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochar and HTC char have physical and chemical properties that are variable, depending on the raw material used and the carbonization technique. Usually, the electrical conductivity (EC) and pH values are similarly low in peat and HTC and are slightly increased in biochar [25].…”
Section: Biochar and Hydrothermal Carbonization Products As Bioresourmentioning
confidence: 99%
“…Several studies reported that biochar in potting media results in the same ornamental plant growth as in peat-based standard substrates [65,145,146]. According to Kern et al [25], char materials must not necessarily remain on the level of a minor ingredient, but have the potential to be used as major constituents. Furthermore, since they are characterized by a high porosity and a high water-holding capacity, these materials may also be usable as a substitute for constituents, which are already established in the growing media market, but which have a limited supply [25,147,148].…”
Section: Greenhouse Ornamental Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar (BC) has been recently proposed as a strong candidate to substitute for peat because of its high porosity, low density and high cation-exchange capacity (Steiner and Harttung, 2014;Vaughn et al, 2015;Kern et al, 2017). Biochar is a carbon (C)-rich material produced by pyrolysis of biomass and has been a major subject of study as a soil amendment in the last decade (Lehmann and Joseph, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for such a spread is probably the higher economical return that is expected per tonne of added (rather expensive) biochar from arable crops than from pastures/ forests. For the same reason, biochar use may well become widespread first as a growing medium constituent in highvalue crops (see Kern et al 2017, this issue) than as a fieldscale soil amendment material.…”
Section: Environmental Representativeness: Climate Land Use and Soilsmentioning
confidence: 99%